Culture Shock in Higher Education: Experiences of Freshmen in Two English Education Departments - Yunika Maulida; Muhammad Jauhari Sofi (EDULANGUE, 2023)
The transition from high schooling to higher education often triggers culture shock among newcomers, particularly those majoring in English education. This study aims to investigate the nature of culture shock experienced by freshmen majoring in English and their coping mechanisms. The study includes four participants—two males and two females—from the English Education Department of two different universities in Pekalongan. Employing a narrative approach, the research unveiled five categories of culture shock: course load, teaching methodologies, learning resources, assignment frequency, and self-confidence. The study also found eight strategies employed by these students to navigate culture shock: personalized learning approaches, embracing mistakes confidently, seeking guidance from seniors, practicing self-disclosure, approaching lecturers for assistance, understanding the education system, refraining from comparisons with peers, and fostering relationships and friendships. These findings offer valuable insights to assist new students in mitigating negative culture shock, while pursuing their English studies. However, due to the contextual limitations, which many not apply to other educational settings, future studies should explore diverse academic backgrounds.